FE-assisted investigation for mechanical behaviour of connections in offshore wind turbine towers. (15th June 2023) - Cheng, Lu; Yang, Fei; Seidel, Marc; Veljkovic, Milan
Highlights: 1. Numerical analyses are performed on three types of bolted connections. 2. The effectiveness of the conventional segment approach is investigated. 3. Sufficient pretension force is beneficial for all three types of connections. 4. The C1 wedge connection is rather insensitive to the variation of pretension force. Abstract: The overall competitiveness of offshore wind turbine towers is significantly influenced by the selection of the connection. The following three types of connections: a conventional bolted ring flange (RF) connection, ring flange connection with defined contact surfaces (RFD), and C1 wedge connection (C1-WC) are considered. A quantitative comparison is made to enhance performance in a specific condition and enable further optimization of these connections in engineering practices. The study compares the tensile behaviour and fatigue performance of these connections by validated finite element (FE) simulation and analysis. The proposed FE modelling is based on a realistic geometry including all contacts present in the connections, steel full-range stress–strain relationship and ductile damage model. The efficiency and accuracy of the FE models are validated through the comparison with the performed tests. Then, a series of parametric FE analyses are carried out to examine the impact of the applied boundary conditions, bolt pretension level, and steel grade on the behaviour of connections. Load-displacement curves, bolt evolution curves, and stress responses are analysed to compare their tensile behaviour. The effectiveness of conventional segment specimen testing is evaluated thoroughly. For the fatigue performance of connections, the results indicate that the segment specimen testing substantially underestimates the fatigue performance of C1-WCs. This discrepancy is essential to be considered in the tower design. It is also noted that C1-WCs are rather insensitive to the variation of pretension force level, which show superiority to avoiding the difficulties associated with typically bolted joints. This research provides in-depth knowledge for the practical application of such connections and further optimization.